2015
DOI: 10.12966/abc.02.06.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Offspring Signature Whistle Similarity and Patterns of Association in Atlantic Spotted Dolphins (Stenella frontalis)

Abstract: -We assessed the degree of similarity between signature whistles of mother and offspring pairs in freeliving Atlantic spotted dolphins (Stenella frontalis). As a means of qualitative evaluation, judges compared the timefrequency contour patterns of signature whistle spectrograms. We also evaluated quantitative measurements of whistle frequency and duration. All five female offspring produced signature whistles that were similar to their mothers' whistles by a least one means of comparison, whereas two of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…According in Bebus and Herzing (2015) average minimum frequency sound of the whistle is 8090 Hz, the average maximum frequency sound whistle 21030 Hz, it indicates the difference between the minimum frequency of the sound of the whistle to the research conducted is 10 Hz, and the difference between the maximum frequency of the sound of the whistle is 100 Hz. In the study conducted by Janik (2000) obtained maximum value Source Level (SL) of the common bottlenose dolphin is 40 dB with a frequency is 12 kHz, this indicates that there are differences in values Source Level (SL) obtained from this study, in this study derive maximum value SL is 29 dB with a frequency is 16 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…According in Bebus and Herzing (2015) average minimum frequency sound of the whistle is 8090 Hz, the average maximum frequency sound whistle 21030 Hz, it indicates the difference between the minimum frequency of the sound of the whistle to the research conducted is 10 Hz, and the difference between the maximum frequency of the sound of the whistle is 100 Hz. In the study conducted by Janik (2000) obtained maximum value Source Level (SL) of the common bottlenose dolphin is 40 dB with a frequency is 12 kHz, this indicates that there are differences in values Source Level (SL) obtained from this study, in this study derive maximum value SL is 29 dB with a frequency is 16 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…Our video footage and some underwater follows show bubbles emanating from calves’ blowholes while they emitted these calls as they approached their mothers after a short separation (see Videoes S1 and S2 in DOI: 10.6084/m9.figshare.7992212). Bubble streams are often used as a cue to identify vocalizing animals (Bebus & Herzing, 2015; Fripp, 2005; Jones, 2014) and in this case the bubble stream revealed that the calves were producing the calls and did so in a repetitive fashion. These vocal patterns are similar to what has been described for calves of bottlenose dolphins, which use signature whistle as contact calls, where calves increase whistle emission as they approach their mothers (Smolker, Mann & Smuts, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of spectrograms of whistle that there are noise or noise in it [7] can be seen in Figure 1, and click sound of dolphins can be seen in (Figure 2). Previous research by looking at whistling sound vocalizations of dolphins and a clicking sound is [8][9][10] bioacoustic research about stidulatory ever done with object Guppy fish [11][12][13][14]. The vocalisation characteristics described above have been found to vary among populations, possibly due to habitat differences, ambient noise, sympatry with other dolphin species, etc.…”
Section: Fisheries and Oceanography Open Access Journalmentioning
confidence: 99%